Nanoscale Based Ti/Aln/Ti/Sio2 Multi-Layer Absorber Coatings For Solar Thermal Devices - Mutawalli, Bello (2022)
A lot of research has been carried out in developing absorber coatings for high temperature solar thermal applications. Yet, high thickness remains serious issue as it leads to high emittance and peel due to poor adhesion at higher temperatures leading to low performance. In this research work, Ti/AlN/Ti/SiO2 multilayer solar absorber coating was deposited onto stainless steel (SS 316L) substrate using Direct Current/Radio Frequency (DC/RF) magnetron sputtering for high temperature solar absorber applications. High purity (99.99%) targets of Ti, AlN and SiO2 were used. To enhance solar absorption, the substrate was modified by simple annealing in air at 600 oC for 1 h and achieved Fe3O4 layer on the surface of the substrate.